Osteoarthritis-Like Changes in Bardet–Biedl Syndrome Mutant Ciliopathy Mice (Bbs1M390R/M390R): Evidence for a Role of Primary Cilia in Cartilage Homeostasis and Regulation of Inflammation - Sheffield, Isaac D.; McGee, Mercedes A.; Glenn, Steven J.; Baek, Da Young; Coleman, Joshua M.; Dorius, Bradley K.; Williams, Channing; Rose, Brandon J.; Sanchez, Anthony E.; Goodman, Michael A.; Daines, John M.; Eggett, Dennis L.; et al. (Frontiers in Physiology, 2018)
Abstract Osteoarthritis (OA) is a debilitating inflammation related disease characterized by joint pain and effusion, loss of mobility, and deformity that may result in functional joint failure and significant impact on quality of life. Once thought of as a simple “wear and tear” disease, it is now widely recognized that OA has a considerable metabolic component and is related to chronic inflammation. Primary cilia have been shown to be cause OA-like changes in Bardet-Biedl Syndrome (BBS) mice. We examined the role of dysfunctional primary cilia in OA in mice through the regulation of the previously identified degradative and pro-inflammatory molecular pathways common to OA. We observed an increase in the presence of pro-inflammatory markers Tgf-1 and HtrA1 as well as cartilage destructive protease Mmp-13 but a decrease in Ddr-2. We observed a morphological difference in cartilage thickness in BBS mice compared to wild type (WT). We did not observe any difference in OARSI or Mankin scores between WT and BBS mice. Primary cilia appear to be involved in the upregulation of biomarkers, including pro-inflammatory markers common to OA.